Dynamic Spatial Small-Target Simulation System with Long-Exit Pupil Distance - Yi Lu; Xiping Xu; Ning Zhang; Yaowen Lv; Hua Geng (Photonics, 2025)
System architecture was developed to solve the issues of short pupil distance and mismatch between the simulated wavelength range and the sensor in the simulator of small targets in space. The system consists of Liquid Crystal on Silicon (LCOS), a Polarizing Beam Splitter (PBS), a dual free-form surface-illumination system, and a long-exit-pupil-distance projection system. The innovatively designed long exit pupil distance projection system can achieve an exit pupil distance of 1250 mm, covering the visible and near-infrared bands from 400 to 950 nm. The dual free-form surface-illumination system reaches a divergence angle of ±4.3° and an illumination non-uniformity of 4.7%. Experimental validation shows that the system’s star position error is better than −3.94″, and the angular distance error between stars does not exceed −7.69″. The radiation simulation accuracy for stars ranging from magnitude 3 to 6 is between −0.049 and 0.085 magnitudes, demonstrating high-precision simulation capabilities for both geometric and radiation characteristics. The research results set a critical theoretical foundation for the development of high-fidelity space target simulators, and the proposed dual free-form surface-design method and wide-spectrum aberration compensation technology provide a new paradigm for precision optical system design.